Modeling and analysis of synergistic effect in thermal conductivity enhancement of polymer composites with hybrid filler. (February 2015) - Chen, Lin; Sun, Ying-Ying; Lin, Jun; Du, Xiao-Ze; Wei, Gao-Sheng; He, Shao-Jian; Nazarenko, Sergei
Abstract: Hybrid filler with proper filler ratio can remarkably improve the thermal conductivity of polymer composites by the synergistic effect. However, there is a lack of an effective mathematical model that could describe such effect or predict the optimal ratio of the hybrid filler. In this paper, a two-step analytical model was developed for calculating the effective thermal conductivity ( keff ) of epoxy composites containing hybrid single-walled carbon nanotubes (SWCNTs) and graphite nanoplatelets (GNPs) filler. Based on the experimental observation in the literature, a unit cell containing a GNP–SWCNTs–GNP sandwich structure was abstracted, and thermal resistance method and effective medium approach were used to derive the model with the assumption that the effective height of the SWNCTs in the unit cell follows the normal distribution. The modeling results were highly consistent with the experiment results in the literature. The synergistic effect was clearly observed and the optimal ratio of hybrid filler could be predicted from the model. Effect of the key parameters on the keff in the model were also analyzed and discussed.